2021
DOI: 10.1155/2021/7336488
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Acute Retinal Necrosis following SARS-CoV-2 Infection

Abstract: Purpose. To report on a case of reactivation of acute retinal necrosis following SARS-CoV-2 infection. Methods. Observational case report. Observations. A 32-year-old female with a distant history of left retinal detachment secondary to necrotizing herpetic retinitis complained of right-eye vision loss, pain, redness, and photophobia. An ophthalmological examination revealed findings consistent with acute retinal necrosis of the right eye. A polymerase chain reaction (PCR) analysis of the right vitreous was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…PCR from the aqueous humor sample was positive for both HSV and VZV. Of note, 4 cases of ARN (3 cases were HSV related, 1 case was VZV related) have been reported after the infection of SARS-CoV-2 (22)(23)(24). The unconceivable risk of aberrant immune reactions leading to the reactivation of HSV or VZV needs to be kept in mind after the COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…PCR from the aqueous humor sample was positive for both HSV and VZV. Of note, 4 cases of ARN (3 cases were HSV related, 1 case was VZV related) have been reported after the infection of SARS-CoV-2 (22)(23)(24). The unconceivable risk of aberrant immune reactions leading to the reactivation of HSV or VZV needs to be kept in mind after the COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during the COVID-19 pandemic, besides reports of neuroretinitis after SARS-CoV-2, there were also reports of reactivation of acute retinal necrosis due to HSV after COVID-19 in few cases [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a PCR analysis of the right vitreous was positive for HSV-2, and the RT-PCR was positive for SARS-CoV-2 RNA. Thus, it was suggested that the SARS-CoV-2 infection might cause the reactivation of a latent HSV infection, with its contralateral involvement in patients who have a prior history of HSV-related acute retinal necrosis [ 51 ].…”
Section: Posterior Segment Of the Eyementioning
confidence: 99%